Bradykinin receptors gene expression in white adipose tissue in nondiabetic patients with coronary artery disease. Issue 4 (June 2018) - Marketou, Maria E.; Kochiadakis, George; Kontaraki, Joanna; Zacharis, Evangelos; Kanoupakis, Emmanouel; Kallergis, Emmanouel; Mavrakis, Hercules; Tsiverdis, Panagiotis; Lempidakis, Dimitris; Konstantinou, John; Fragkiadakis, Konstantinos; Chlouverakis, Gregory; et al.
Abstract : Objectives: Adipose tissue plays a key role in cardiovascular physiology. Kinin receptors are important determinant of the effect of adiposity on endothelial function and cardiovascular function. We examined the gene expression levels of kinin receptors in the subcutaneous white adipose tissue (sWAT) of nondiabetic patients with and without coronary artery disease (CAD). Patients and methods: We evaluated 21 patients with CAD (13 men, age: 68±8 years) and 23 patients without CAD (15 men, age: 66±5 years) who underwent catheterization through the femoral route. sWAT biopsies were obtained from the site of vessel puncture before the procedure and analyzed for bradykinin receptor type 1 ( BKR1 ) and 2 ( BKR2 ) gene expression by real-time quantitative PCR. Results: Although BKR2 expression levels did not differ significantly (413.12±532.41 in CAD patients vs. 378.33±534.45 in controls, P =NS), BKR1 expression in sWAT was significantly greater in patients with CAD (352.69±455.12 vs. 46.5±46.7, P <0.05). Notably, BKR1 gene expression levels showed a significant positive correlation with BMI ( r =0.45, P <0.002) and total cholesterol levels ( r =0.53, P <0.001), and a negative correlation with fasting blood glucose ( r =−0.4, P =0.006). Conclusion: There is a divergence in BKR1 gene expression in sWAT between patients with and without CAD and is associated with metabolic parameters. More studies are needed to determine the pathophysiological role of BKRs in adipogenesis, fat expansion, and atheromatous disease.